Strengths and durability performances of blended cement concrete with TiO2 nanoparticles and rice husk ash. (30th August 2019) - Praveenkumar, T.R.; Vijayalakshmi, M.M.; Meddah, M.S.
Highlights: Using pozzolanic materials such as RHA and TiO2 in concrete reduce clinker consumption and the CO2 generated. The combination of 10%RHA and various amounts of TiO2 improved strength and durability performances of concrete. 3% TiO2 nanoparticles was found to be the optimum replacement level. Abstract: Sustainable development, climate change and the extensive extraction and consumption of non-renewable mineral resources are the greatest contemporary challenges facing humankind, especially construction industry. Reducing the mining and consumption of raw materials, and CO2 emission generated by the production of Portland cement clinker as well as improving concrete performance are now achievable targets even with the use of various recycled and by-product materials in a partial replacement of virgin materials. In the present study, concrete designed with Titanium dioxide (TiO2 ) Nanoparticles and rice husk ash (RHA) as pozzolanic materials used in a partial replacement of Portland cement (PC) has been investigated. RHA was used in a single amount of 10% while TiO2 nanoparticles was incorporated at different replacement levels varying from 0 to 5% as a partial replacement of PC. The morphological and mineralogical characteristics of TiO2 Nanoparticles were analysed using Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD), respectively. The blended cement concrete mixes have been assessed in terms of mechanical and durability performances including compressive, Flexural and Splitting Tensile strengths, resistance to Acid attack and Chloride Penetration. The results revealed that concrete mixes with a combination of 10%RHA and 3% TiO2 Nanoparticles as a partial replacement of PC showed the highest strengths and durability performances. Increasing the TiO2 Nanoparticles beyond 3% has resulted in a drop in strengths and durability properties. Thus, this replacement of 3% nano-TiO2 might be considered as the optimum replacement level.